Postmodern views on the Early Music practice: performance, pedagogy and society - Michel, Melodie (Analitica. Rivista online di studi musicali, 2017)
The Early Music movement has generated a shift in performance practices of Western Art music and in its pedagogy. Musical analyze, if it became a key in the production of Historically Informed Performances, is always accompanied by a serious contextualization. In this article I will show how practices in Early Music can be seen as essentially postmodern (Jameson, Butt), recalling principles of deconstruction (Norris) for both its epistemology and its pedagogy. Early Musicians build on their knowledge of pre-modern music theories to promote non-canonized forms through an "insistent questioning of [their] own methods and practices" (Tomlinson). This postmodern attitude in knowledge transmission reveals a deep shift in social practices related to fields as diverse as politics, work organization or economics, and the recent debates between professional musicians are the mirror of difficulties to define one’s positioning, especially when founded over such a ungraspable and moveable background. Oscillating between modern ideologies inherited from the Enlightenment and pre-modern concepts of art consumption, between literacy and orality (Goody), this practice, defined by acts of deconstruction, struggles to construct its identity. I consider these attempts as reflecting the peregrinations of a twenty-first century epistemology in search of itself. In this essay, I partly based my work on ethnographic researches in Southern Europe, alongside scholarship readings and textual analyzes.